Short‐ and Long‐term Opioid Use in Patients with Oral and Oropharynx Cancer. (6th November 2018) - McDermott, Jessica D.; Eguchi, Megan; Stokes, William A.; Amini, Arya; Hararah, Mohammad; Ding, Ding; Valentine, Allison; Bradley, Cathy J.; Karam, Sana D.
Abstract : Objective: Opioid use and abuse is a national health care crisis, yet opioids remain the cornerstone of pain management in cancer. We sought to determine the risk of acute and chronic opioid use with head and neck squamous cell cancer (HNSCC) treatment. Study Design: Retrospective population‐based study. Setting: Surveillance, Epidemiology and End Results (SEER)–Medicare database from 2008 to 2011. Subjects and Methods: In total, 976 nondistant metastatic oral cavity and oropharynx patients undergoing cancer‐directed treatment enrolled in Medicare were included. Opiate use was the primary end point. Univariate and multivariable logistic analyses were completed to determine risk factors. Results: Of the patients, 811 (83.1%) received an opioid prescription during the treatment period, and 150 patients (15.4%) had continued opioid prescriptions at 3 months and 68 (7.0%) at 6 months. Opioid use during treatment was associated with prescriptions prior to treatment (odds ratio [OR], 3.28; 95% confidence interval [CI], 2.11‐5.12) and was least likely to be associated with radiation treatment alone (OR, 0.35; 95% CI, 0.18‐0.68). Risk factors for continued opioid use at both 3 and 6 months included tobacco use (OR, 2.23; 95% CI, 1.05‐4.71 and OR, 3.84; 95% CI, 1.44‐10.24) and opioids prescribed prior to treatment (OR, 3.84; 95% CI, 2.45‐5.91 and OR, 3.56; 95% CI, 1.95‐6.50). Oxycodone prescribed as the first opioid was the least likely to lead to ongoing use at 3 and 6 months (OR, 0.33; 95% CI, 0.17‐0.62 and OR, 0.26; 95% CI, 0.10‐0.67). Conclusion: Patients with oral/oropharyngeal cancer are at a very high risk for receiving opioids as part of symptom management during treatment, and a significant portion continues use at 3 and 6 months after treatment completion.